1995
DOI: 10.1111/j.1745-4557.1995.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

PERFORMANCE OF AN INSTRUMENT DESIGNED FOR, AND EVALUATION OF METHODS TO ASSESS, PEACH FRUIT IMPACT BRUISE SUSCEPTIBILITY1

Abstract: A simple, inexpensive device was fabricated for imposing drop impact loads on fruit and tested using a 0.5 J load on peach [(Prunus persica (L.) Batsch] fruit harvested at two maturity stages. The device consists of an electromagnet to secure a metallic mass above the fruit, a height adjustment forpositioning the mass, a foot pedal switch for interrupting current to the electromagnet, allowing the mass to strike the fruit, and a thick aluminum base toprevent fruit movement upon impact. Following impact, fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although several past studies proposed to clarify the relationship between specific shock conditions and the probability of damage of fresh produce by drawing DBCs (Maness et al, 1995;Mathew and Hyde, 1997;Lu and Wang, 2007;Kitazawa et al, 2014), the current result is an advance in clarifying the relationship between Vc, PAcc, and BA for apple fruit.…”
Section: The Current Results Also Suggest That Various Combinations Ofmentioning
confidence: 98%
“…Although several past studies proposed to clarify the relationship between specific shock conditions and the probability of damage of fresh produce by drawing DBCs (Maness et al, 1995;Mathew and Hyde, 1997;Lu and Wang, 2007;Kitazawa et al, 2014), the current result is an advance in clarifying the relationship between Vc, PAcc, and BA for apple fruit.…”
Section: The Current Results Also Suggest That Various Combinations Ofmentioning
confidence: 98%
“…Thus, there are some studies dealing with the different response of several fruit varieties or cultivars to mechanical damage (Maness et al, 1995) intentionally caused mechanical damage in five peach cultivars and found significant differences among the diameters and depths of the injuries. Similar results have been reported for Asian pear (Chen et al, 1987) and apple (Ericsson and Tahir, 1996b).…”
Section: Fruit Speciesmentioning
confidence: 97%